Two types of whistler waves in the hall reconnection region. Issue 7 (25th July 2016) - Huang, S. Y.; Fu, H. S.; Yuan, Z. G.; Vaivads, A.; Khotyaintsev, Y. V.; Retino, A.; Zhou, M.; Graham, D. B.; Fujimoto, K.; Sahraoui, F.; Deng, X. H.; Ni, B.; et al.
Abstract: Whistler waves are believed to play an important role during magnetic reconnection. Here we report the near‐simultaneous occurrence of two types of the whistler‐mode waves in the magnetotail Hall reconnection region. The first type is observed in the magnetic pileup region of downstream and propagates away to downstream along the field lines and is possibly generated by the electron temperature anisotropy at the magnetic equator. The second type, propagating toward the X line, is found around the separatrix region and probably is generated by the electron beam‐driven whistler instability or Čerenkov emission from electron phase‐space holes. These observations of two different types of whistler waves are consistent with recent kinetic simulations and suggest that the observed whistler waves are a consequence of magnetic reconnection. Key Points: Two types of whistler waves are observed in the reconnection diffusion region First one is in pileup region, and second one is around separatrix Whistlers are the consequences of magnetic reconnection